THE RUSSIAN SATIRICAL POETIC TRADITION IN THE WORKS OF LEV LOSEV: FROM ANTIOCHUS CANTEMIR TO SASHA CHERNY - Shermuхamedova Nasiba Almasovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: the article examines the peculiarities of the influence of the Russian satirical tradition in the range from A.Cantemir to S.Cherny on the work of L.Losev, in particular, the peculiarities of using the poetic techniques he inherited.